Clinical experience with white blood cell‐PET/CT in autosomal dominant polycystic kidney disease patients with suspected cyst infection: A prospective case series. Issue 7 (24th July 2018) - Kim, Hyunsuk; Oh, Yun Kyu; Park, Hayne Cho; Park, Seokwoo; Lee, Soojin; Lee, Ho‐young; Hwang, Young‐Hwan; Ahn, Curie
Abstract: Aims: Cyst infection (CI) is a common problem in patients with autosomal dominant polycystic kidney disease (ADPKD). Localization is of great importance in CI. We describe the clinical experience with [18F] FDG‐labelled white‐blood cell (WBC) PET/CT in detecting CI in ADPKD. Methods: Nineteen ADPKD patients (M:F = 7:12) suspected of having CI were enrolled in this prospective study. All underwent WBC‐PET/CT and MRI or CT. The degree of their WBC accumulation was evaluated from the maximal standardized uptake value of cystic wall. Results: Cyst infection was diagnosed in 14 cases [definite ( n = 6), probable ( n = 1), or possible ( n = 7); kidney ( n = 11), or liver ( n = 3)]. There was no difference in fever or laboratory findings (White blood cell count, C‐reactive protein, culture results, and eGFR). The blood culture was positive only in a subset of CI patients ( n = 4). Cyst fluid culture yielded bacterial growth in 80% of aspirates. WBC‐PET/CT detected 64% of CI cases, whereas conventional imaging, 50%. WBC‐PET/CT showed false‐positive results in two of five cases with no CI. The reasons for false negatives with WBC‐PET/CT were poor host immune reaction, low virulence, or prior antibiotic therapy. Haemorrhagic cysts were the most common cause of false positivity in WBC‐PET/CT. However, WBC‐PET/CT detected CI in three cases, in which the conventional imaging failed to find CI. Conclusions: Clinical information may play little role in the diagnosis of CI. WBC‐PET/CT can be used to detect CI with better sensitivity in ADPKD patients, circumventing the exposure to contrast media. Summary at a Glance: This single‐centre prospective case‐series describes the clinical and diagnostic characteristics of ADPKD patients with a suspected renal/hepatic cyst infection and found WBC‐PET/CT to have better sensitivity in detecting cyst infection than conventional imaging.